A cluster analysis of tourist attractions in Spain: Natural and cultural traits and implications for global tourism - Dana-Nicoleta Lascu; Lalita A. Manrai; Ajay K. Manrai; Allison Gan (European Journal of Management and Business Economics (EJM&BE), 2018)
Purpose: Natural and cultural tourism are important motivators for international tourism. Spain has impressive tourist attractions that are outstanding on the natural and cultural tourism dimensions. The purpose of this paper is to identify traits of the most attractive destinations in Spain and to understand the relative importance of natural, cultural, and dual (natural and cultural) attractions to target consumers. Design/methodology/approach: The authors compare the level of tourism in the 17 major regions of Spain and identify the key natural, cultural, and dual attractions using a two-step cluster analysis to ascertain the relative importance of the three types of attractions. Findings: The findings of the cluster analysis suggest that natural attractions had the highest importance, followed by dual attractions, with cultural attractions having the lowest importance in affecting the level of tourism in a region. The study identified four categories of regions resulting from "high vs low" total number of attractions by "high vs low" levels of tourism (operationalized via the number of tourist-nights). The regions with high levels of tourism were either located in the bodies of water (a group of islands) or on ocean/sea(s) surrounding Spain. The study suggests placing greater emphasis on promoting cultural attractions in Spain. Practical implications: The findings suggest that there is a need to put more emphasis on promoting the cultural attractions in Spain. Spain is a diverse country with huge potential for tourism from people all over the world, due to its diverse geography and rich history. Originality/value: To the best of the authors' knowledge, this is the first study that analyzes 17 regions of Spain in relation to their tourism characteristics, identifying attractions that are not sufficiently leveraged, and suggesting strategies for identifying opportunities for the tourism industry in Spain.
Keywords: 650; Cultural attractions; Dual attractions; Natural attractions; Tourist attractions